2008
DOI: 10.1111/j.1365-2672.2008.03738.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of disperse textile dye Brown 3REL by newly isolatedBacillussp. VUS

Abstract: Aims:  To isolate the potential micro‐organism for the degradation of textile disperse dye Brown 3 REL and to find out the reaction mechanism. Methods and Results:  16S rDNA analysis revealed an isolate from textile effluent contaminated soil as Bacillus sp. VUS and was able to degrade (100%) dye Brown 3REL within 8 h at static anoxic condition. A significant increase in the activities of lignin peroxidase, laccase and NADH‐DCIP reductase was observed up to complete decolourization of Brown 3REL. The optimum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(56 citation statements)
references
References 24 publications
10
46
0
Order By: Relevance
“…On the other hand, 100% degradation of dye Brown 3REL by Bacillus sp. VUS was achieved within eight hours at static anoxic condition [17]. This bacterium was also able to degrade 80% of dye in textile effluent.…”
Section: Biological Treatmentmentioning
confidence: 89%
“…On the other hand, 100% degradation of dye Brown 3REL by Bacillus sp. VUS was achieved within eight hours at static anoxic condition [17]. This bacterium was also able to degrade 80% of dye in textile effluent.…”
Section: Biological Treatmentmentioning
confidence: 89%
“…Gan et al (2011) reported that different enzymes such as protocatechuate dioxygenases and aromatic ring hydroxylases are responsible for the cleavage of aromatic rings. Similarly, Dawkar et al (2008) reported that laccases are involved in the demethylation of aromatic compounds. Hydroxylation dioxygenases have been reported to be involved in oxidative deamination reactions forming phenol like compounds (Lin et al, 2010).…”
Section: Biodegradation Via Oxidative Processesmentioning
confidence: 93%
“…Interest in the bioremediation of pollutants using bacteria has intensified in recent years, as many researches demonstrated the efficacy of bacterial bioremediation over fungal and actinomycetes. Many bacteria capable of reducing azo dyes reported were isolated from textile effluent contaminated sites [35]. The effluent sample collected from Ankleshwar textile industries, Ankleshwar, Gujarat, India, was black in color, with pungent smell and pH of slightly above neutral level and was within the permissible limits.…”
Section: Physico-chemical Characterization Of Textile Effluentmentioning
confidence: 99%